Pembelajaran Sains yang Rahmatan Lil ‘Alamin - Salafudin, Salafudin (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2018)
Abstract Science and technology have great benefits for mankind. But science can also be a punishment for humans. In other words, science has positive and negative values for humans. Efforts need to be made to minimize the negative side of science and increase its benefits, so that science is present as a blessing for the universe. Science that is rahmatan lil ‘alamin is a science that can implement the values of rahmatan lil ‘alamen thus bringing humanity to a life that is prosperous, safe, peaceful and egalitarian. Such science is expected to bring harmony to life. Not only brings prosperity to humans, but also to all beings on earth. Efforts to present the science of rahmatan lil ‘alamien are carried out with science learning integrated with rahmatan lil ‘aalmaien Islamic values. Science learning that rahmatan lil ‘alamin has several characteristics, among others: presenting a non-pragmatic intention in learning science, linking faith to God with natural phenomena, science learning is contextual, science learning is associated with values, culture and beliefs. The implementation rahmatan lil ‘aalamin science learning requires the hard work of all parties considering the current reality of science learning still oriented towards the West. This is due to the lack of concrete examples of learning models and alternative science books. Abstrak Sains dan teknologi memberi manfaat yang besar bagi umat manusia. Namun sains juga bisa menjadi azab bagi manusia. Dengan kata lain, sains mempunyai nilai positif dan negatif bagi manusia. Perlu dilakukan ikhtiar untuk meminimalisasi sisi negatif sains dan memperbesar manfaatnya, sehingga sains hadir sebagai rahmat bagi semesta. Sains yang rahmatan lil ‘alamin merupakan sains yang bisa mengimplementasikan nilai-nilai rahmatan lil ‘alamien sehingga membawa umat manusia pada kehidupan yang sejahtera, aman, damai dan egaliter. Sains yang demikian diharapkan akan memunculkan harmoni kehidupan. Bukan hanya memunculkan kesejahteraan bagi manusia, melainkan juga bagi seluruh makhluk di muka bumi. Upaya menghadirkan sains yang rahmatan lil ‘aalamien dilakukan dengan pembelajaran sains terintegrasi dengan nilai-nilai islam rahmatan lil ‘aalmaien. Pembelajaran sains yang rahmatan lil ‘alamin mempunyai beberapa karakteristik antara lain: menghadorkan niat yang tidak pragmatis dalam mempelajari sains, mengaitkan keimanan kepada Tuhan dengan fenoma alam, pembelajaran sains bersifat kontekstual, pembelalajaran sains dikaitkan dengan nilai, budaya dan keyakinan. Implementasi pembelajaran sains yang rahmatan lil ‘aalamin memerlukan kerja keras semua pihak mengingat realitas saat ini pembelajaran sains masih berkiblat ke Barat. Hal ini disebabkan minimnya contoh konkret model pembelajaran maupun buku sains alternatif.